2020
DOI: 10.1007/s13205-020-2083-z
|View full text |Cite
|
Sign up to set email alerts
|

Herbal ethosomal gel containing luliconazole for productive relevance in the field of biomedicine

Abstract: This study includes development, characterization, and optimization of herbal ethosomal formulation. The aim of the present study is to develop drug loaded ethosomes capped with Azadirachta indica (neem) which, was further incorporated in Carbopol 934 K thereby, resulting in the formation of ethosomal gel. The formulation is aimed to express effective treatment against fungal infection. The build was formulated using drug (Luliconazole), soyalecithin, ethanolic neem extract and propylene glycol. In total nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Many researchers have worked on nanoparticulate systems such as nanosponges and microemulsion based gel 9,12 . Kumar et al worked on luliconazole nanocrystals loaded hydrogel for improvement of dissolution and anti‐fungal activity, 13 Dave et al reported improved dermal delivery of luliconazole from herbal ethosomal gel of luliconazole 14 and Kaur et al prepared vesicular‐based gel of luliconazole for enhanced topical delivery 11 . Nanostructured lipid carriers (NLCs) are an upgrade to the ordinary carrier systems such as microemulsions and liposomes as it offers advantage of exhibiting higher drug loading capacity, large surface area and small size 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have worked on nanoparticulate systems such as nanosponges and microemulsion based gel 9,12 . Kumar et al worked on luliconazole nanocrystals loaded hydrogel for improvement of dissolution and anti‐fungal activity, 13 Dave et al reported improved dermal delivery of luliconazole from herbal ethosomal gel of luliconazole 14 and Kaur et al prepared vesicular‐based gel of luliconazole for enhanced topical delivery 11 . Nanostructured lipid carriers (NLCs) are an upgrade to the ordinary carrier systems such as microemulsions and liposomes as it offers advantage of exhibiting higher drug loading capacity, large surface area and small size 15 .…”
Section: Introductionmentioning
confidence: 99%
“…This variation was already observed in previous studies. As an example, Dave et al developed several ethosomes with gel formulations, but the most similar formula with this study revealed a viscosity of 7063 ± 2.8 cP [ 43 ]. Another example revealed that the addition of ethosomes in Carbopol gel affects its flow and viscoelastic behavior [ 44 ].…”
Section: Resultsmentioning
confidence: 65%
“…A homogeneous thin film was obtained on the wall of the flask. The resulting drug-lipid film was then rehydrated with distilled water and appropriate concentration of ethanol [6][7][8][9]. First, preliminary formulation of ethosomes was prepared using different concentrations of ethanol (20-40%), lipid (30-50 mg) and cholesterol (0-5 mg).…”
Section: Preparation Of Repaglinide Ethosomes Using Thin-film Hydrationmentioning
confidence: 99%
“…A 1% w/w Carbopol 940 gel was prepared as vehicle for repaglanide ehosomes The ethosomal formulation was added to the hydrated carbopol solution, with stirring until a homogeneous ethosomal gel was obtained. pH of the gel was adjusted to neutral by triethanolamine and stirred slowly [7].…”
Section: Ethosomal Gel Formulationmentioning
confidence: 99%